There and back again – The return of the nasal mite Halarachne halichoeri to seals in German waters. (August 2019) - Reckendorf, Anja; Wohlsein, Peter; Lakemeyer, Jan; Stokholm, Iben; von Vietinghoff, Vivica; Lehnert, Kristina
Abstract: The nasal mite Halarachne halichoeri (Acari; Halarachnidae) is adapted to live in the marine environment with pinnipeds as its primary host and can cause different levels of upper respiratory disease in both harbour seals ( Phoca vitulina ) and grey seals ( Halichoerus grypus ). Historical reports of H. halichoeri occurring in seals from German waters date back to the end of the 19th century. However, with the disappearance of the grey seal from German waters as a consequence of human over-exploitation, the mite vanished from the records and the fauna found in Germany for more than a century. Although a stranding network has been monitoring marine mammal health along the German coasts since the mid 1980s with extensive post-mortem investigations, this study reports the first and subsequent findings of H. halichoeri in grey and harbour seals from the North and Baltic Sea from 2014 onwards. The re-emergence of this endoparasitic mite in North and Baltic Sea habitats seems to have occurred simultaneously with the recolonisation of its primary host, the grey seal. During the course of its recolonisation, it was probably transmitted to harbour seals sharing the same haul-out sites. Molecular analyses showed a high similarity of rDNA sequences with H. halichoeri collected from sea otters ( Enhydra lutris ) in the USA. However, more thorough analyses of additional gene loci are required to fully assess the exchange and diversity of this parasite between geographically isolated regions and species. Graphical abstract: Image 1 Highlights: First finding of endoparasitic seal mite H. halichoeri in Germany after >100 years. Recolonisation of North and Baltic Sea in unison with primary host grey seal. Morphological comparison with century-old museum specimens. Minor histopathological alterations in upper respiratory tract associated. High genetic similarity of ITS-2 with H. halichoeri from sea otters in the USA.